Effect of enriching live feeds with HUFA on growth and survival of clownfish Amphiprion ocellaris (Cuvier, 1830) larvae - Lam, Ho Son; Hue, Nguyen Thi Nguyet; An, Dinh Truong; Khanh, Phan Thi (Vietnam Journal of Marine Science and Technology, 2019)
The aims of this study was to evaluate the effect of HUFA-enriched live feed in rearing Nemo fish larvae (Amphiprion ocellaris), 5 treatments were set up (each treatment was repeated in triplicate) with 5 concentrations of HUFA (Super Selco) (0, 50, 100, 150 and 200 ppm). After 45 days of culture with HUFA-enriched live feeds of different concentrations, the total length-TL as well as the specific growth rate (SGRL) in body length and survival rate of Nemo fish larvae in the treatments had significant differences (p < 0.05). In the enriched live prey diet of 100 ppm Selco, TL, SGRL and the survival rate of Nemo fish larvae were the highest (10.01 ± 0.150 mm, 7.20 ± 0.099%/day and 82.67 ± 0.881%, respectively). Lowest TL, SGRL and survival rate were obtained in larvae fed with the control diet (8.65 ± 0.051 mm, 6.23 ± 0.041%/day and 68.70 ± 0.881%, respectively). The results of this experiment suggest that the optimal Selco concentration used to enrich live feeds for Nemo fish larvae is 100 ppm, which can improve the production efficiency of Nemo stock.